Analisis Tingkat Kecacatan Produk Sarung Merek Donggala Motif Songket Menggunakan Metode Seven Tools dan Failure Effect And Analysis (FMEA) Di PT Bintang Tri Putratex - Sumiati; Mochammad; Rahmawati, Nur (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
Bintang Tri Putratex is a company engaged in the manufacturing industry producing songket sarongs. In the songket sarong production process, defects such as sarong stains, color defects, broken threads and pattern defects are still found which affect the quality. The aim of this research is to determine the level of defects for each defect so that we can provide suggestions for improvements to reduce defects in songket sarong products. The method used is Seven Tools and Failure Mode and Effect Analysis (FMEA). Seven Tools include check sheets, stratification, histograms, Pareto charts, Pareto diagrams, scatter diagrams, control charts, and fishbone diagrams. Then proceed with FMEA analysis to get suggestions for corrective action. Based on research results at Seven Tools, it is known that the most dominant level of defects in songket sarongs is sarong stains (38.4%), then color defects (30.64%), broken threads (16.49%) and pattern defects (14 .47%). Based on the results of the Failure Mode and Effect Analysis (FMEA) research, it is known that the cause of the highest problem with RPN 216 is that the machine is rarely maintained with proposed recommendations for improvement, namely making a regular schedule for carrying out maintenance on the machine. Keywords: Quality Control, songket sarong, Seven Tools, FMEA